Cluster of DnaA Boxes Involved in Regulation of Streptomyces Chromosome Replication: from In Silico to In Vivo Studies - Smulczyk-Krawczyszyn, Aleksandra (American Society for Microbiology, 2006)
In Streptomyces coelicolor, replication is initiated by the DnaA protein in the centrally located oriC region and proceeds bidirectionally until the replication forks reach the ends of the linear chromosome. We identified three clusters of DnaA boxes (H69, H24, and D78) which are in a relatively short segment of the chromosome centered on the oriC region. Of the clusters analyzed, D78 exhibited the highest affinity for the DnaA protein; the affinity of DnaA for the D78 cluster was about eightfold higher than the affinity for oriC. The high-affinity DnaA boxes appear to be involved in the control of chromosome replication. Deletion of D78 resulted in more frequent chromosome replication (an elevated ratio of origins to chromosome ends was observed) and activated aerial mycelium formation, leading to earlier colony maturation. In contrast, extra copies of D78 (delivered on a plasmid) caused slow colony growth, presumably because of a reduction in the frequency of initiation of chromosome replication. This suggests that the number of high-affinity DnaA boxes is relatively constant in hyphal compartments and that deletion of D78 therefore permits an increased copy number of either the chromosomal origin region or a plasmid harboring the D78 cluster. This system conceivably influences the timing of decisions to initiate aerial mycelial formation and sporulation.